TEACHER STRATEGY IN TEACHING ENGLISH VOCABULARY TO VERY YOUNG LERANERS - Rossy Rosalina, - (2012)
The research is entitled "Teacher's strategy in Teaching English Vocabulary to Very Young Learner" (A descriptive study of teacher's strategy at one a preschool in Bandung)" which is aimed to find out teacher's strategy in teaching English vocabulary to young learner and difficulties faced by the teacher during teaching and learning process. To collect the data, there were some techniques applied: Observation (video recording), interviews and document analysis. They were analyzed qualitatively. The research findings showed that there were several strategies applied by the teacher in teaching vocabulary to very young learner. The strategies are (1) Drilling, (2) Total Physical Responses (TPR), (3) Art and Craft, (4) Storytelling, (5) Game and (6) Song. The difficulty faced by the teacher was Adjustment to children's language. From findings of the research it can be conclude that teaching English vocabulary to very young learner in that preschool still lack of teacher's strategies. Therefore, to achieve the learning effectively especially in teaching English vocabulary to very young learner, it is necessary for the teacher to apply more than one strategies and activities. It is also recommended to other researchers who conduct the same topic may use the systematic sequences in teaching English vocabulary above in different level of learners.